UTILIZATION OF MPU6050 FOR STRUCTURAL VIBRATION MONITORING IN HIGH-RISE BUILDINGS - Axel Irving Yoshua; Yohanes Calvinus; Hugeng (Universitas Tarumanagara, 2026)
The purpose of this study is to develop a system for monitoring vibrations in high-rise buildings using an ESP32 microcontroller and an MPU6050 sensor. The study focuses on analyzing the structural response of buildings to dynamic loads and external influences. Therefore, this research employed a vibration measurement experiment on the 20th floor of the Main Building of Universitas Tarumanagara for one hour and produced 13 observation data points recorded at five-minute intervals. The MPU6050 sensor is an accelerometer and gyroscope capable of detecting linear acceleration and angular rotation on the X and Y axes. The obtained data were then processed to identify vibration patterns and the maximum amplitude on each axis. The results showed differences in the vibration patterns between the X and Y axes, with a maximum value of 0.0237 g on the Y-axis and 0.0234 g on the X-axis. The greater fluctuations on the Y-axis indicate that the Y-axis is more susceptible to vibrations caused by atmospheric conditions, such as wind and/or human activities. Although the detected vibrations were relatively small, with a total magnitude of 0.0237 g, these results support the importance of regular building vibration monitoring to maintain occupant comfort and structural stability. The research location was limited to the measurement point on the 20th floor of the Main Building, and the testing duration was limited to one hour. Weather conditions may also affect the measurement results. Further research with a longer duration and measurements at various locations within the building is required to obtain more comprehensive data. The direct implication of this study is the importance of an automatic sensor-based monitoring system that can quickly identify potential structural disturbances and thereby help ensure the comfort of building occupants. Abstrak Tujuan dari penelitian ini adalah untuk membuat sistem yang dapat melakukan pemantauan pada getaran pada bangunan bertingkat dengan menggunakan mikrokontroler ESP32 dan sensor MPU 6050. Fokus penelitian untuk menganalisis respon struktur bangunan terhadap beban dinamis dan pengaruh eksternal dapat dianalisis. Oleh karena itu, penelitian ini menggunakan eksperimen pengukuran getaran di lantai 20 gedung induk Universitas Tarumanagara selama satu jam dan menghasilkan 13 data pengamatan dengan interval pencatatan sekitar lima menit. Sensor MPU6050 merupakan akselerometer dan giroskop yang dapat mendeteksi percepatan linier dan rotasi sudut pada sumbu X dan Y. Data yang diperoleh kemudian diolah untuk mengidentifikasi pola getaran serta amplitudo maksimum pada setiap sumbu. Hasil yang diperoleh menunjukkan bahwa adanya perbedaan pola perubahan antara sumbu X dan sumbu Y, dengan nilai maksimum 0,0237 g pada sumbu Y dan 0,0234 g. Fluktuasi besar pada sumbu Y menunjukkan bahwa sumbu Y lebih rentan terhadap getaran. Meskipun getaran yang terdeteksi relatif kecil dan memiliki nilai magnitudo total 0,0237g, hasil ini mendukung pentingnya pemantauan getaran bangunan secara berkala untuk menjaga kenyamanan penghuni dan stabilitas struktural. Lokasi penelitian dibatasi pada lokasi pengujian di lantai 20 gedung utama; durasi pengujian dibatasi selama satu jam. Penelitian lebih lanjut diperlukan dengan durasi yang lebih lama dan pengujian di berbagai lokasi di gedung agar data lebih komprehensif. Implikasi langsung dari penelitian ini adalah pentingnya sistem pemantauan berbasis sensor otomatis yang dapat dengan cepat mengidentifikasi kemungkinan gangguan struktural dan dengan demikian memastikan kenyamanan penghuni di dalam gedung.